Tiny programming language to improve assembly generation for automation equipment - Metrôlho, J.C.M.M. (2011)
The development time in industrial informatics systems, within industry environments, is a very important issue for competitiveness. The usage of adequate targetspecific programming languages is very important because they can facilitate and improve developers’ productivity, allowing solutions to be expressed in the idiom and at the level of abstraction of the problem’s domain. In this paper we present a target-specific programming language, which was designed to improve the design cycle of code generation, for an industrial embedded system. The native assembly code, the new language structure and their constructs, are presented in the paper. The proposed targetspecific language is expressed using words and terms that are related to the target’s domain and consequently it is now easier to program, understand and to validate the desired code. It is also demonstrated the language efficiency by comparing some code described using the new language against the previous used code. The design cycle is improved with the usage of the target-specific language because both description and debug time are significantly reduced with this new software tool. This is also a case of university-industry partnership.